Bis-Iridoids: Occurrence, Chemophenetic Evaluation and Biological Activities—A Review - Claudio Frezza; Alessandro Venditti; Daniela De Vita; Marcella Guiso; Armandodoriano Bianco (Molecules)
In this work, the first review paper about bis-iridoids was presented. In particular, their detailed occurrence, chemophenetic evaluation and biological activities were reported. To the best of our knowledge, two hundred and eighty-eight bis-iridoids have been evidenced so far, bearing different structural features, with the link between two seco-iridoids sub-units as the major one. Different types of base structures have been found, with catalpol, loganin, paederosidic acid, olesoide methyl ester, secoxyloganin and loganetin as the major ones. Even bis-irdioids with non-conventional structures like intra-cyclized and non-alkene six rings have been reported. Some of these compounds have been individuated as chemophenetic markers at different levels, such as cantleyoside, laciniatosides, sylvestrosides, GI-3, GI-5, oleonuezhenide, (Z)-aldosecologanin and centauroside. Only one hundred and fifty-nine bis-iridoids have been tested for their biological effects, including enzymatic, antioxidant, antimicrobial, antitumoral and anti-inflammatory. Sylvestroside I was the compound with the highest number of biological tests, whereas cantleyoside was the compound with the highest number of specific biological tests. Bis-iridoids have not always shown activity, and when active, their effectiveness values have been both higher and lower than the positive controls, if present. All these aspects have been deeply discussed in this paper, which also shows some critical issues and even suggests possible arguments for future research, since there is still a lot unknown about bis-iridoids.